Coronavirus disease 2019: a revolution in biological triage in the emergency setting - Manoochehry, Shahram; Saboori, Fatemeh; Faraji, Mehrdad; Behzadnia, Mohammad Javad (Universa Medicina, 2020)
Triage is a familiar concept for all who work at the forefront of the treatment of patients and the emergency medical staff know their duty in different situations including crisis and epidemics. Accordingly, the coronavirus outbreak has also a major effect on the emergency department (ED) as it changes the routine ED function. Our main question was what are the main triage challenges in the recent pandemic and how we could overcome these challenges? Therefore, a search of the main Web databases was performed for articles published till May 1st, 2020 using various related keywords. In various steps, the title, summary, methodology, results, and discussion of the selected studies were assessed to find out the recent triage strategies in the COVID-19 outbreak. Hence, all the available and related English review articles, case series, and experimental studies were evaluated. Among 200 studies initially reviewed, 59 met the study criteria for the final assessment. COVID-19Â puts a significant load on public health services and potential damage to social and psychiatric situations by marked morbidity and mortality. In line with the various presentations and according to the changing of the COVID-19 epidemic to a worldwide pandemic problem, the management and treatment protocols changed several times. Accordingly, the local and even global hospital protocols were changed as well. The first simple concept of coronavirus triage in an emergency department is the separation of COVID-19 infected patients from the others. This approach has been practiced around the world. Changing the ED layout from a usual triage or fast track set to an isolated room is necessary for such a pandemic situation. It is very important to consider staff communication and the application of PPE. All the efforts should be taken to protect patients as well as the medical staff from unnecessary exposure and infection; this serves to keep the health facilities working well in the outbreak and diffusion of SARS-CoV-2.